2017
DOI: 10.1177/2056305117706785
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation Into Facebook “Liking” Behavior An Exploratory Study

Abstract: , Mark Zuckerberg, CEO of Facebook (FB), announced that a billion people had used FB in 1 day to connect with friends and family, a milestone that was reached about a decade after the launch of the social media platform in 2004 (facebook.com). This rapid growth of FB brought with it an increase in the use of its "social media buttons" such as the "Like" and "Share" features. In May 2013, FB estimated that 4.5 billion Likes were generated daily by its users, a 67% increase from August 2012 (facebook.com). Like … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 56 publications
0
35
0
2
Order By: Relevance
“…We have derived the established and validated measures from existing literature with minor modifications. The measurement scales of enjoyment, passing time, information seeking, self-presentation, social presence, and social interaction are adopted and modified from Zhou et al [10], Gan [7], and Ozanne et al [11]. The measurement of liking behavior is modified from Gan [7] and Ozanne et al [11], and the measurement scales of subjective norms and continuous usage intentions for Facebook come from Al-Jabri et al [19] and Li et al [20].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…We have derived the established and validated measures from existing literature with minor modifications. The measurement scales of enjoyment, passing time, information seeking, self-presentation, social presence, and social interaction are adopted and modified from Zhou et al [10], Gan [7], and Ozanne et al [11]. The measurement of liking behavior is modified from Gan [7] and Ozanne et al [11], and the measurement scales of subjective norms and continuous usage intentions for Facebook come from Al-Jabri et al [19] and Li et al [20].…”
Section: Methodsmentioning
confidence: 99%
“…In addition, De Oliveira and Huertas [22] suggested that subjective norms, social identity, group norms, entertainment, and interpersonal interconnectivity positively impact user satisfaction on Facebook. Moreover, a number of studies have empirically validated SNS research stating that user behavioral intentions are predicted by different aspects of gratification, such as hedonic gratification, content gratification, utilitarian gratification, and social gratification [11,20,24]. Different research points out that each gratification contains different dimensions.…”
Section: Uses and Gratification Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…Bununla birlikte makalelerin, pek çok farklı disiplin ve çalışma alanına uzandığını görülür. Araştırmaların beşte birlik kısmına denk düşen ‚diğer‛ kategorisi, sosyoloji, spor, sağlık, edebiyat, güvenlik, turizm, hukuk, ilahiyat, bilişim, enformatik, psikoloji Facebook'ta zaman kavramı (Kaun & Stiernstedt, 2014), Facebook'un duygusal yayılımı (Hallinan, Brubaker & Fiesler, 2019), Facebook'ta beğeni pratiği (Ozanne et al 2017), güvenlik ayarlarının yönetimi (Suh & Hargittai, 2015), bağlantı mühendisliği (van Dijck, Çalışmaların veri toplama tekniğine bakıldığında en çok kullanılan teknik, anket (%31,2) ve içerik analizidir (%25,5). Anlamlı bir çoğunluk oluşturan diğer bir teknik ise, ölçek oluşturma ya da belli bir ölçeğin sınanması (%16,3) şeklindedir.…”
Section: Bulgular Ve Yorumunclassified